Perakitan Varietas Hibrida Jagung Manis Berdaya Hasil Tinggi dan Tahan Terhadap Penyakit Bulai - Sriani Sujiprihati; Muhamad Syukur; Andi Takdir Makkulawu; R Neny Iriany (Institut Pertanian Bogor, 2012)
Sweet corn is a result of recessive mutation which occurs naturally in gene that controls the conversion of sugar into starch in corn seed endosperm. There are 3 main genes that affect corn sweetness, namely sugary gene (su), sugary enhancer gene (se), and shrunken gene (sh2). This study aims to obtain a general combining ability value for the sweet corn lines, which will be the parent in diallel crosses; obtain the information of general combining ability, specific combining ability, and heterosis value for sweet corn lines; and obtain one or more promising single cross hybrids that will be potential for high yield and resistance to downy mildew disease. The study was conducted from April 2009 until November 2011 at the Experimental Field Centre for Cereal Plant Study (BALITSEREAL), Maros, South Sulawesi. The results showed that five genotypes had moderately high yield: Mr4/SC/BC4-3-1B, Mr14/SC/BC4-6-1B, Mr11/SC/BC4-3-1B, Mr14/SC/BC3-8-1B, and Mr12/SC/BC4-6-1B. The attack level of downy mildew that was classified as resistant has 0 to 7% rate. The combination of crosses that produce better productivity than all the varieties are: C × A (Mr11/SC/BC4-2-1B-1 × Mr12/SC/BC4-5-B-1), A × D (Mr12/SC/BC4-5-B-1 × Mr11/SC/BC4-2-1B-1), E × B (Mr12/SC/BC3-3-1B -1 × Mr14/SC/BC4-6-1B-1), and B × D (Mr11/SC/BC4-2-1B-1 × Mr14/SC/BC4-6-1B-1 ). Five hybrids can be continued for the preliminary testing of yields. Twelve candidate varieties do not have yield different than the checked varieties, so it can proceed to a multilocation trials to explore the advantages that can be released as new varieties.